Participatory varietal selection in finger millet - Halaswamy, B.H.; Gowda, B.T.S.; Seetharam, A.; Virk, Daljit S.; Witcombe, John R. (CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation, 2001)
Finger millet (Eleusine coracana L. Gaertn.) is an important small millet for rainfed areas in India. A dozen varieties have been released for cultivation but there is little adoption by farmers, particularly in the Chitradurga and Bellary districts of Karnataka state where the present study was conducted. Participatory rural appraisal (PRA) showed that all farmers wanted higher grain and fodder yields, while only 8% mentioned resistance to diseases. Varieties of 105 to 110 days duration with moderate to high tillering and compact-top, in-curved ears were more acceptable. The PRA al so showed that there was a varietal monoculture of PR 202 from Andhra Pradesh state.